Challenges to the Administrative Service of Municipalities in Bulgaria - Kirilova, Katia (Research Papers, 2018)
The report presents the principles and standards for administrative services. The state of administrative services in the municipalities is analyzed, using data for the provided administrative services and electronic administrative services. The status of the websites of selected municipalities has been examined. The challenges faced by the municipal administration are presented, being grouped into thematic groups. An emphasis is placed on the problems set out in the strategic documents, with data from the reports on the state of the administration in Bulgaria for 2015 presented and 2016 years. There are conclusions and recommendations are given for improving administrative services in municipalities.
Keywords: Complex administrative service; Administrative services; E-government